MUSYRIF PARENTING STYLE IN INTEGRATED ISLAMIC HIGH SCHOOL NUR HIDAYAH DORMITORY - Bahtiar, Luth Hafizh; Jinan, Mutohharun; Azani, Mohammad Zakki (Muhammadiyah University Press, 2020)
Nur Hidayah integrated Islamic high school Surakarta is an educational institution that provides dormitories. Several years ago there were not as many students living as now. Nearly 80% of students live in guesthouses. This study aims to identify and examine the roles of supervisors (musyrif) on student achievement. This research is field research conducted by Integrated Islamic High School (SMA IT) Nur Hidayah Surakarta. This research is implementing interviews, observation, and documentation and then using a phenomenological and analytical approach. This study showed that this school tended to use democratic parenting. In educational institutions, no parenting style only uses one pattern, so in fact, educational institutions apply moderate parenting or combine all parenting patterns with a divided composition. The special role of the supervisor members (musyrif) at Nur Hidayah is to implement a home learning system. The special feature of this system allows students to be more intense to interact with the surrounding community. This system makes it possible for them to be prepared in real life. Given that intellectual intelligence is no longer the main thing, there must be a balance between social and emotional intelligence. Nur Hidayah's musyrif parenting provides opportunities and stimuli for students to be able to develop academic and non-academic abilities. Specific positive activities that exist in each type of Dormitory will support their development in learning such as taá¸¥fiz, foreign language practice, and so on. Besides that, the composition of moderate parenting (combining three styles of parenting) that has been made in such a way will make fostering, supervision, learning, and education more effective and efficient.